Estudo da reticulação de blendas de goma de linhaça/ágar utilizando nanocristais de celulose como reforço - Prado, Natália Soares (2017)
Nowadays, due to the incentive and the requirement for the use of sustainable products, the blends and nanocomposites from biopolymers appear as a proposal for application in several fields, such as: packaging, biomedicine and agriculture. In this sense, flaxseed gum/agar blends were developed using glutaraldehyde as a crosslinker and cellulose nanocrystals as reinforcement, produced by casting method. Preliminary tests were fulfilled varying the amount of crosslinker agent and plasticizer, changing the pH of the medium in order to insert crosslinks in the polymer structure and consequently decrease the hydrophilicity of the samples. The development of the blends in acid medium by setting the mass proportions of additives (30 wt.% glycerol and 15 wt.% glutaraldehyde relative to the final mass for each film) and varying the polymers proportions (75/25, 50/50 and 25/75 GL/AG). The nanocomposites were obtained from each formulation (blends and control samples) with the addition of 2, 4 and 8% w/w of cellulose nanocrystals (NC). Films and blends were characterized by Differential Scanning Calorimeter, Thermal Gravimetric Analysis, X-ray Diffraction and Attenuated Total Reflectance with Fourier Transforms Infrared Spectroscopy techniques in order to assess possible interactions and organization of the system. The effect of the crosslinking in the polymer matrices, their blends and the nanocomposites were evaluated through the interaction with water by the solubility test, water vapor absorption, contact angle and water vapor permeability. The morphology of the samples was studied by the Scanning electron microscopy and, finally, the tensile test was performed to evaluate the mechanical performance of the samples. The endothermic events observed in the DSC curves may be associated with new interactions established in the polymeric systems. The thermogravimetric curves showed increased thermal stability for the control films and crosslinked blends in acid media. The X-ray diffractograms presented a diffuse pattern of the amorphous material. The infrared spectra did not present specific bands of crosslinking, only those being in the original structure of the polysaccharides. MEV images showed good aggregation and dispersion for blends and nanocomposites. Tests performed on the interaction of the films with water show that crosslinking in acid media led to a lower solubility for the flax gum formulation. The insertion of agar, as well as, the insertion of NC contributed to a lower water absorption and improvement in the mechanical tensile properties. The 50/502%NC and 50/504%NC formulations showed increased tensile rupture, Young's Modulus and elongation thus demonstrating results that justify both blends and nanocomposites originated from these. Moreover, with the different morphologies obtained in this study it is possible to extend the application range for the proposed formulations.